2019
DOI: 10.1038/s41598-018-36934-8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying outbreaks of Porcine Epidemic Diarrhea virus through animal movements and spatial neighborhoods

Abstract: The spread of pathogens in swine populations is in part determined by movements of animals between farms. However, understanding additional characteristics that predict disease outbreaks and uncovering landscape factors related to between-farm spread are crucial steps toward risk mitigation. This study integrates animal movements with environmental risk factors to identify the occurrence of porcine epidemic diarrhea virus (PEDV) outbreaks. Using weekly farm-level incidence data from 332 sow farms, we applied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 56 publications
1
103
0
Order By: Relevance
“…The uncontrolled ASF epidemic in Eastern Europe poses a serious threat to the pig industry throughout Europe, Central Asia and even China. Some studies have shown that using machine learning algorithms can help to better understand the factors associated with disease transmission and establish appropriate predictive models (Ding, Fu, Jiang, Hao, & Lin, ; Jiang et al, ; Machado et al, ; Safarishahrbijari & Osgood, ). A better understanding of the disease‐associated factors is a crucial step towards the definition of strategies for control and eradication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncontrolled ASF epidemic in Eastern Europe poses a serious threat to the pig industry throughout Europe, Central Asia and even China. Some studies have shown that using machine learning algorithms can help to better understand the factors associated with disease transmission and establish appropriate predictive models (Ding, Fu, Jiang, Hao, & Lin, ; Jiang et al, ; Machado et al, ; Safarishahrbijari & Osgood, ). A better understanding of the disease‐associated factors is a crucial step towards the definition of strategies for control and eradication.…”
Section: Discussionmentioning
confidence: 99%
“…China. Some studies have shown that using machine learning algorithms can help to better understand the factors associated with disease transmission and establish appropriate predictive models (Ding, Fu, Jiang, Hao, & Lin, 2018;Jiang et al, 2018;Machado et al, 2019;Safarishahrbijari & Osgood, 2019 with BF search method was used to search for the optimal feature subset. By comparing the calculation times of the model before and after feature selection, it can be found that the model calculation speed can be accelerated after using feature selection.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these researchers evaluated transmission, beyond animal movement, that included wind speed, fomites, weather and topographical features. They found that disease risk could be predicted at the farm receiving animals and that disease risk, in a neighbourhood of farms, could be affected by long‐distance animal movement as well as the landscape and weather features, within a neighbourhood (Machado et al, ). This PEDV model demonstrates how models can be used to both better understand transmission dynamics and inform professionals seeking to prevent and control the spread of infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hamer et al [7] use ML algorithms to predict spatio-temporal epidemic spareness of pathological diseases. AI tools for predicting outbreak in cardiovascular diseases [8,9], Influenza [10], and epidemic Diarrhea [11] is also proposed. A nice review of the AI application on such a prediction is reported in [12].…”
Section: Related Workmentioning
confidence: 99%